From Doxastic to Epistemic: A Typology and Critique of Qualitative Interview Styles - Berner-Rodoreda, Astrid; Bärnighausen, Till; Kennedy, Caitlin; Brinkmann, Svend; Sarker, Malabika; Wikler, Daniel; Eyal, Nir; McMahon, Shannon A. (SAGE Journals, 2022)
This article was published in the Qualitative Inquiry [© The Author(s) 2018) ] and the definite version is available at: https://doi.org/10.1177/1077800418810724 The Journal's website is at: https://journals.sagepub.com/doi/10.1177/1077800418810724